ANALYSIS QUALITY OF HUMAN RESOURCES, WORK PROFESSIONALISM, AND COMMUNICATION AS SUPPORTING FACTORS FOR IMPROVING PERFORMANCE OF AVIATION TRAINING CENTER - Agus Iwan Mulyanto (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2020)
The quality of human resources, work professionalism, communication has an influence on the performance of education and employment center employees in airlines both partially and simultaneously. The research approach used in this study is a quantitative approach. The aviation training center population was 79 employees and 75 people were taken as respondents with the sampling method used was simple random sampling or simple random samples. The method of data analysis uses multiple linear regression analysis. The results of testing and analysis conducted stated that the quality of human resources has a positive and significant effect on employee performance, work professionalism has a positive and significant effect on employee performance and communication has a positive and significant effect on employee performance. Simultaneously the quality of human resources, work professionalism, and communication support employee performance.